Morphological study of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) eggs by X-ray computed microtomography. (November 2019) - de Morais, Lilian Mirian Oliveira; Jussiani, Eduardo Inocente; Zequi, João Antonio Cyrino; dos Reis, Paulo José; Andrello, Avacir Casanova
Highlights: Ae. aegypti and Ae. albopictus eggs were first studied by micro-CT. Several parameters of morphological interest were determined. Some parameters are unprecedented in the literature. It was possible to anatomically differentiate the eggs by micro-CT. Abstract: Aedes aegypti and Aedes albopictus are vectors of several arboviruses responsible for causing dengue, chikungunya, Zika, and yellow fever viruses and microcephaly, resulting in a public health problem in several countries worldwide. Even in this scenario, studies on the morphology of mosquito eggs are still lacking. In this paper, X-ray microtomography was used to study mosquito egg morphology. Several parameters such as length, surface area, volume, area-by-volume ratio, eccentricity and center of mass of the eggs were determined. The results obtained showed that micro-CT is an efficient technique for the morphological study of insect eggs and provides information that cannot be obtained with other techniques.